Activating the Role of Dialogue Education in Promoting Human Values among High School Students from Teachers' Perspective: An Educational Proposal - Alhothali, Huda M (Humanities and Social Sciences Letters, 2022)
The present research paper aims to identify the role, activation methods, and obstacles of dialogue education in promoting human values among female high school students. It makes a proposal to activate dialogue education and promote human values among high school female students. The author adopted the descriptive-analytical approach and used a questionnaire to define the reality, activation requirements, and obstacles. The results showed the low role of dialogue education in promoting human values among high school female students; most items were rated ‘low’. The obstacles were identified, and the overcrowded classroom was ranked first. Moreover, the activation requirements were defined, and transforming the teacher from a mere instructor into a negotiator and a creative educational environment innovator for students was ranked first. The paper recommended establishing a specialized center for education and dialogue to improve and support values, in general, and human values, in particular, inside and outside the school.